Advances in the management of malignant glioma recurrence - Nawrocki, Sergiusz; Cieślak, Ewa (Contemporary Oncology/Współczesna Onkologia, 2006)
Since virtually all malignant gliomas relapse after primary treatment the management of relapsing glioma is a common clinical dilemma. Before making a decision on choice of surgery, chemotherapy or radiotherapy as a treatment option one should consider additional imaging studies to exclude nonmalignant lesions such as radiation necrosis. Standard CT and NMR studies are not sufficient in this context and should be supplemented with NMR spectroscopy, PET, SPET, etc. Secondary surgery should be considered in patients in good shape, with relapse localized in the previously irradiated area. Chemotherapy based on nitrosurea or temozolomide may prolong the patient’s life and improve its quality in selected patients. The emergence of molecular profiling has made it possible to select patients with higher chances of responding to chemotherapy. New targeted therapies inhibiting signal transduction through EGFR, interfering with angiogenesis and other molecules which have been developed on the basis of the expanding knowledge of glioma molecular progression pathways are being studied in clinical trials. Radiotherapy used in the management of relapsing glioma should be highly conformal and include brachytherapy, stereotactic radiotherapy and IMRT conformal radiotherapy. New functional imaging studies are opening exciting possibilities of modulation of radiation dose in relation to hypoxia, angiogenesis area, etc.